2007
DOI: 10.1038/nn1959
|View full text |Cite
|
Sign up to set email alerts
|

Daytime sleep condenses the time course of motor memory consolidation

Abstract: Two behavioral phenomena characterize human motor memory consolidation: diminishing susceptibility to interference by a subsequent experience and the emergence of delayed, offline gains in performance. A recent model proposes that the sleep-independent reduction in interference is followed by the sleep-dependent expression of offline gains. Here, using the finger-opposition sequence-learning task, we show that an interference experienced at 2 h, but not 8 h, following the initial training prevented the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
397
6
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(453 citation statements)
references
References 49 publications
42
397
6
4
Order By: Relevance
“…Positive offline effects, which we observed only in the anodal tDCS group, are thus not a ubiquitous phenomenon in skill acquisition. Nevertheless, positive offline effects have garnered a great deal of attention in recent years as they have been reported in several influential studies of skill consolidation with finger-sequencing tasks (8,42). To the best of our knowledge, there has been little comment about why some skill tasks show a warm-up decrement whereas others show consolidation.…”
Section: Discussionmentioning
confidence: 99%
“…Positive offline effects, which we observed only in the anodal tDCS group, are thus not a ubiquitous phenomenon in skill acquisition. Nevertheless, positive offline effects have garnered a great deal of attention in recent years as they have been reported in several influential studies of skill consolidation with finger-sequencing tasks (8,42). To the best of our knowledge, there has been little comment about why some skill tasks show a warm-up decrement whereas others show consolidation.…”
Section: Discussionmentioning
confidence: 99%
“…Naps, in contrast to caffeine, have been shown to enhance not only alertness and attention, but also some forms of memory consolidation. In particular, naps (daytime sleep between 5-90minutes) appear to improve performance on non-medio-temporal lobe dependent, procedural skills (Mednick et al 2002;Mednick et al 2003;Korman et al 2007;Nishida et al 2007). Mednick and colleagues reported that a mid-day nap can also reverse perceptual deterioration that builds with repeated within-day testing (Mednick et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, the results suggest that basic mechanisms of plasticity necessary for movement sequence learning, and its consolidation into long-term "how to" memory are preserved in moderatesevere patients with TBI, even in individuals with low functional baseline performance. Korman et al (2007) found, in healthy individuals, that the "offline" overnight improvements in performance, following a single training session, were on the order of the contribution of within-session gains. The patients with TBI in the current study, showed a pattern similar to that of the healthy controls ( Figure 3B) of both within-session and betweensession, consolidation phase, gains, although the high betweenindividuals variance and the small number of participants resulted in only marginally significant changes.…”
Section: Discussionmentioning
confidence: 90%
“…In both young (Korman et al, 2007) and older (Korman et al, 2015) healthy adults an interval of sleep has been implicated as a necessary factor in advancing procedural memory processes and the expression of delayed, "offline" gains in the FOS learning task. An association between sleep disturbances and motor learning has been demonstrated in patients with obstructive sleep apnea, with marked impairment in consolidation (Landry et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation